Analysis of Mathematical Representation Skills Based on Student Learning Activities in Hands on Activity Assisted Pbl Learning Model - Meilon, Beny; Mariani, Scolastika; Isnarto, Isnarto (Unnes Journal of Mathematics Education Research, 2019)
Mathematical representation is an important aspect in learning mathematics. Problem based learning, one of the learning models that can be applied to improve the ability of mathematical representation and student learning activities. The objectives of this study were (1) to test and analyze the effectiveness of PBL learning assisted by hands on activity on students 'mathematical representation abilities, (2) to describe the ability of students' mathematical representation based on learning activities. This research uses mixed method research with concurrent embedded design. Quantitative research and qualitative research go hand in hand with quantitative research as the primary method. The research subjects were class X students of SMA 1 Wonotunggal. The results of the study show that the class with PBL learning assisted by hands on activity achieves an average, and complete classics reaching more than 75%. The mean difference test shows the students' mathematical representation of classes with PBL learning assisted hands on activity better than classes with expository learning methods. Subjects who have high and moderate activities are able to fulfill all indicators of mathematical representation ability. Subjects who have less activity have not been able to meet the indicators of mathematical representation ability. Indicators that have not been fulfilled are symbolic and verbal representations.